2011
DOI: 10.1038/nature09932
|View full text |Cite
|
Sign up to set email alerts
|

Structure of mammalian AMPK and its regulation by ADP

Abstract: The heterotrimeric AMP-activated protein kinase (AMPK) plays a key role in regulating cellular energy metabolism; in response to a fall in intracellular ATP levels it activates energy producing pathways and inhibits energy consuming processes1. AMPK has been implicated in a number of diseases related to energy metabolism including type 2 diabetes, obesity and, most recently, cancer 2,3,4,5,6. AMPK is converted from an inactive to catalytically competent form by phosphorylation of the activation loop within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
864
2
14

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 797 publications
(929 citation statements)
references
References 32 publications
33
864
2
14
Order By: Relevance
“…Adenosine 5' monophosphate‐activated protein kinase (AMPK) serves as a cellular energy sensor, which is composed of a catalytic α subunit and regulatory β and γ subunits (Xiao et al ., 2011). The role of AMPK in preventing aging/senescence has been suggested in many studies (Apfeld et al ., 2003; Stenesen et al ., 2013; Ido et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Adenosine 5' monophosphate‐activated protein kinase (AMPK) serves as a cellular energy sensor, which is composed of a catalytic α subunit and regulatory β and γ subunits (Xiao et al ., 2011). The role of AMPK in preventing aging/senescence has been suggested in many studies (Apfeld et al ., 2003; Stenesen et al ., 2013; Ido et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although each molecule of bound AXP interacts with side chains from more than one CBS repeat, a useful convention (Kemp et al 2007) is to number the sites according to the CBS repeat bearing the aspartate residue interacting with the ribose ring. Recent binding studies have helped to define the functions of the three sites (Xiao et al 2011). Site 1 binds all three AXPs with similar high affinities and, based on the concentrations of AMP that cause allosteric activation, binding at this site appears to be responsible for this effect, which is only observed with AMP Xiao et al 2011).…”
Section: Mammalian Ampk-structure and Regulationmentioning
confidence: 99%
“…The "a hook" region of this linker interacts with AMP or ADP bound at site 3 ( Fig. 3; Xiao et al 2011). Phosphorylation of a serine that lies within a flexible loop within the a-carboxy-terminal domain (a-CTD; Ser485 in human a1) appears to inhibit phosphorylation at Thr172 (Horman et al 2006).…”
Section: Mammalian Ampk-structure and Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Our structure-based mutagenesis studies have demonstrated that two of the three nucleotide-binding sites, γ-site 3 and γ-site 4, are important for AMPK allosteric activation. Xiao et al [8] reported the structure of an active AMPK heterotrimer, comprising the kinase domain, AID and the regulatory α-linker of the α-subunit in addition to the core fragment, which revealed additional intersubunit interactions involving the activation loop of the kinase domain and a small segment within the α-linker. However, in the same study, it was concluded that mammalian AMPK does not contain an AID domain, inconsistent with our results [3].…”
Section: Dear Editormentioning
confidence: 99%